Deposition model for chronological records - Ramsey, C (Elsevier, 2008)
Long-term sedimentary sequences provide a wealth of useful information for research into the palaeo-environment, especially in relation to past climate change. Shorter records provide similar information in many archaeological contexts. However if such records are to be used to provide precise timing of events, and more critically the relative timing between different records, methods are needed to provide accurate and precise age-depth models for these sequences. Given the imprecision of individual calibrated radiocarbon determination it is necessary to use the information we have about the deposition process to refine our chronologies and also to provide interpolation between dated levels in any sequence. Even with layer counted chronologies, the uncertainties are sometimes hard to quantify. This paper outlines a range of Bayesian models for deposition which have been implemented in the computer programme OxCat. These models can be used to combine information from the sediments themselves with radiocarbon or other dating information. Such models have the potential to integrate information between different records and provide a coherent chronology on which to base environmental or archaeological research.